Cobalt‐Iron‐Manganese Catalysts for the Conversion of End‐of‐Life‐Tire‐Derived Syngas into Light Terminal Olefins - Falkenhagen, Jan P. (Chemistry, 2018)
Co‐Fe‐Mn/γ‐Al(2)O(3) Fischer–Tropsch synthesis (FTS) catalysts were synthesized, characterized and tested for CO hydrogenation, mimicking end‐of‐life‐tire (ELT)‐derived syngas. It was found that an increase of C(2)‐C(4) olefin selectivities to 49 % could be reached for 5 wt % Co, 5 wt % Fe, 2.5 wt % Mn/γ‐Al(2)O(3) with Na at ambient pressure. Furthermore, by using a 5 wt % Co, 5 wt % Fe, 2.5 wt % Mn, 1.2 wt % Na, 0.03 wt % S/γ‐Al(2)O(3) catalyst the selectivity towards the fractions of C(5+) and CH(4) could be reduced, whereas the selectivity towards the fraction of C(4) olefins could be improved to 12.6 % at 10 bar. Moreover, the Na/S ratio influences the ratio of terminal to internal olefins observed as products, that is, a high Na loading prevents the isomerization of primary olefins, which is unwanted if 1,3‐butadiene is the target product. Thus, by fine‐tuning the addition of promoter elements the volume of waste streams that need to be recycled, treated or upgraded during ELT syngas processing could be reduced. The most promising catalyst (5 wt % Co, 5 wt % Fe, 2.5 wt % Mn, 1.2 wt % Na, 0.03 wt % S/γ‐Al(2)O(3)) has been investigated using operando transmission X‐ray microscopy (TXM) and X‐ray diffraction (XRD). It was found that a cobalt‐iron alloy was formed, whereas manganese remained in its oxidic phase.